Global research hotspots and trends in non-surgical treatment of adolescent idiopathic scoliosis over the past three decades: a bibliometric and visualization study - Xu, Jie; Chen, Meng; Wang, Xin; Xu, Lin; Luo, Xiaobing (Frontiers in Pediatrics, 2024)
In recent years, research on the non-surgical treatment of AIS has been increasingly conducted. To the best of our knowledge, this field doesn't yet have a comprehensive and structured pulse combing analysis. In order to provide inspiration and resources for subsequent researchers, we thus reviewed the literature studies on the non-surgical treatment of AIS from the previous thirty years and highlighted the hotspots and frontiers of research in this field. Methods: Main using Citespace 6.1 software, the data from the core dataset of the WOS database pertaining to the non-surgical management of AIS from 1990 to 2022 was gathered, displayed, and analyzed. -2 -Results: 839 papers in all were included in the literature. With 215 papers, the USA came in first place. Chinese Univ Hong Kong ranked first with 32 papers. Research hotspots are adolescent idiopathic spondylitis, Schroth-based physiotherapy-specific exercise efficacy, curve development, Cobb angle, TLSO brace-based clinical efficacy, quality of life, reliability, health-related quality of life questionnaires, finite element biomechanical models, follow-up, and clinical guidelines.There aren't many studies that compare the clinical effectiveness of various non-surgical treatments, and because of variations in inclusion eligibility standards and outcome measures, these studies cannot be directly compared. In addition, the inconsistency of existing growth potential and progression risk assessment systems further affects comparative studies of clinical efficacy; it is recommended to establish primary assessment indicators centered on patient treatment outcomes (including appearance, disability, pain, and quality of life), as well as standardized scoliosis progression risk assessment criteria.